Experimental and Computational Modeling of the Effects of Voice Therapy Using Tubes - Horáček, J; Radolf, V; Laukkanen, A-M (Journal of speech, language, and hearing research, 2019)
Purpose Phonations into a tube with the distal end either in the air or submerged in water are used for voice therapy. This study explores the effective mechanisms of these therapy methods. Method The study applied a physical model complemented by calculations from a computational model, and the results were compared to those that have been reported for humans. The effects of tube phonation on vocal tract resonances and oral pressure variation were studied. The relationships of transglottic pressure variation in time Ptrans ( t) versus glottal area variation in time GA( t) were constructed. Results The physical model revealed that, for the phonation on [u:] vowel through a glass resonance tube ending in the air, the 1st formant frequency ( F1 ) decreased by 67%, from 315 Hz to 105 Hz, thus slightly above the fundamental frequency ( F0 ) that was set to 90-94 Hz . For phonation through the tube into water, F1 decreased by 91%-92%, reaching 26-28 Hz, and the water bubbling frequency Fb ≅ 19-24 Hz was just below F1 . The relationships of Ptrans ( t) versus GA( t) clearly differentiate vowel phonation from both therapy methods, and show a physical background for voice therapy with tubes. It is shown that comparable results have been measured in humans during tube therapy. For the tube in air, F1 descends closer to F0 , whereas for the tube in water, the frequency Fb occurs close to the acoustic-mechanical resonance of the human vocal tract. Conclusion In both therapy methods, part of the airflow energy required for phonation is substituted by the acoustic energy utilizing the 1st acoustic resonance. Thus, less flow energy is needed for vocal fold vibration, which results in improved vocal efficiency. The effect can be stronger in water resistance therapy if the frequency Fb approaches the acoustic-mechanical resonance of the vocal tract, while simultaneously F0 is voluntarily changed close to F1.
Keywords: Speech Acoustics; Speech Therapy; anatomické modely; lidé; Glottis; Phonation; akustika řeči; Female; fonace; hlasový trénink; Computer Simulation; Humans; Voice Training; mužské pohlaví; počítačová simulace; ženské pohlaví; Models, Anatomic; řečová terapie; Lung; Male; plíce; glottis